Rehabilitacija mladega moškega s tetraplegijo, z ulceroznim kolitisom in hudo osteoporozo - Ščavničar, Ana (Rehabilitacija (Ljubljana), 2010)
The case report presents a young patient suffering from ulcerous colitis with associated complications, severe osteoporosis and ankylosing spondylitis. In May 2009, he suffered an "innocent" fall down the hill that caused fracture ofthe 4th and 5th cervical vertebrae. He is now tetraplegic. After various complications during acute care, there was a difficult start of complex rehabilitation.
Keywords: ankilozirajoči spondilitis; osteoporoza; rehabilitacija; tetraplegija; ulcerozni kolitis; vocational rehabilitation